Å skape et hjem – kvinners plass i den tidlige institusjonsbyggingen. Nord-Norge før 1940 - Hamran, Torunn (Novus forlag, 2007)
Scandinavian welfare research has paid more and more attention to the role played by women in building institutions for children, the sick and the elderly. The new institutions were generally called ”homes” and it was precisely this linkage between women and homes that may have led to clear perceptions of what the new ”homes” were like. Concepts like motherliness, homeliness and intimacy are presented as important characteristics, despite (or because of ) the lack of empirical evidence. Historical research has shown that the home was highly idealised around the turn of the last century, but this idealisation was prescriptive and did not necessarily reflect real homes. The aim of this article is to argue that an institution, or any social system, cannot be perceived in isolation from the particular parties that created them – or from the place where they were created. Only then is it possible to say something about which or whose concept of a home was (attempted) realised. A phenomenological perspective on the home will often take as its starting point people’s need for identity, intimacy, security and meaningfulness. From a sociological point of view, the aspects that phenomenology pinpoints as important are created through time-consuming work and relevant categories can be connected with how the work is organised. ”A home” can be a lot of things, so the analysis must draw on both material, structural and symbolic aspects. Kvinners bidrag i utformingen av velferdsstaten har fått stadig større oppmerksomhet i skandinavisk velferdsforskning. Gjennom humanitære og religiøse organisasjoner bidro de til å opprette institusjoner for barn, syke og gamle, i stort antall. De nye institusjonene ble gjennomgående kalt ”hjem”, og nettopp forbindelsen mellom kvinne og hjem ser ut til å ha ført til klare oppfatninger av hvordan de nye ”hjemmene” var. Institusjonene omtales som hjemlignende tilbud etter en familiær modell eller resonnementet føres enda et skritt videre ved å beskrive ”hjemmene” som typisk for en virksomhet ...